Analisis Kredit Macet Dan Penanganannya: Prespektif Hukum Ekonomi Syariah - Alfina Rahmatun Nida (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2021)
Credit in banking is an agreement for borrowing money by the customer and then the customer pays the debt gradually every month according to the time agreed by both parties. Customers who have obtained credit facilities from the bank are not fully able to return their debts smoothly according to the previously agreed upon maturity. As a result of customers who are unable to pay their debts, their credit becomes suspended or becomes bad. If you are late in paying installments, there is a fine so that you will be trapped in a debt containing usury which is haram.